Design Mechanisms in Increasing the Growth of Plus Batik MSME's Instagram Accounts - Melati, Karina Rima; Hardoyo; Lala Hucadinota Ainul Amri (Mediakita, 2023)
Social media is increasingly becoming a mainstay for Micro, Small, and Medium Enterprises (MSMEs) to do marketing, branding, and even sales. At least 42% of MSMEs in Indonesia have used social media or digital platforms. In the Covid-19 pandemic, using social media to carry out business activities is increasingly inevitable. As an SME that started its business at the end of 2020, Plus Batik utilizes social media, especially the Instagram platform (plusbatik.id), to increase awareness as a batik brand from Jogja. Excellent social media planning, primarily through content mapping and editorial planning, is the key to successful account growth. This research was conducted to analyze how Plus Batik carries out the mechanism of content mapping and editorial planning. Then, by monitoring and evaluating, how do the content mapping and editorial planning increase the growth of @plusbatik.id’s social media accounts? This study investigates the problems and objectives of the @plusbatik.id account using empirical methods with a qualitative approach and then designs content mapping and editorial planning for three periods. Then produce three content types: 'Post' is created with a call to action, 'Story' uses the features of questions, quizzes, polls, and votes, and 'Reel' utilizes hashtags currently being widely discussed. The account's growth is obtained through algorithm analysis of the Insight feature.